Stem Cells and Platelet-Rich Plasma Enhance the Healing Process of Tendinitis in Mice - Rosangela Alquieri Fedato; Júlio César Francisco; Gabriel Sliva; Lúcia de Noronha; Márcia Olandoski; Jose Rocha Faria Neto; Priscila Elias Ferreira; Rossana Baggio Simeoni; Eltyeb Abdelwahid; Katherine Athayde Teixeira de Carvalho; Luiz César Guarita-Souza (Stem Cells International)
Objective. Achilles tendon pathologies occur frequently and have a significant socioeconomic impact. Currently, there is no evidence on the best treatment for these pathologies. Cell therapy has been studied in several animal models, and encouraging results have been observed with respect to tissue regeneration. This study is aimed at evaluating the functional and histological effects of bone marrow stem cell or platelet-rich plasma implantation compared to eccentric training in the treatment of Achilles tendinopathy in rats. Methods. Fourty-one male Wistar rats received collagenase injections into their bilateral Achilles tendons (collagenase-induced tendinopathy model). The rats were randomly divided into four groups: stem cells (SC), platelet-rich plasma (PRP), stem cells+platelet-rich plasma (SC+PRP), and control (eccentric training (ET)). After 4 weeks, the Achilles tendons were excised and subjected to biomechanical and histological analyses (Sirius red and hematoxylin-eosin staining). Results. Biomechanical assessments revealed no differences among the groups in ultimate tensile strength or yield strength of the tendons (p=0.157), but there were significant differences in the elastic modulus (MPa; p=0.044) and maximum tensile deformation (p=0.005). The PRP group showed the greatest maximum deformation, and the SC group showed the highest Young’s modulus (elasticity) measurement. In histological analysis (hematoxylin-eosin and Sirius red staining), there were no differences among the groups. Conclusion. PRP and SC+PRP yielded better biomechanical results than eccentric training, showing that these treatments offer better tend function outcomes. This theoretical rationale for the belief that cell therapies can serve as viable alternatives to current treatments chronic fibrotic opens the door for opportunities to continue this research.